Lifestyle and Social Factors Exacerbated on the Prevalence of Mood Disorders and Functional Dyspepsia Among Neonatal Nurses in China - Huang, Zhen-peng; Huang, Fang; Wang, Mei-jun; Tang, Chuan-zhuang; Huang, Jiang-ping; Ling, Juan; Li, Shan-e; Wei, Su-qiao; Lei, Hai-hua; Li, Jing-jing; Lan, Xiu (Frontiers in Psychiatry, 2022)
Background: Nursing is a high-stress occupation that can have an impact on mental health, particularly for neonatal nurses. Job-related stress factors and work-related behaviors have played a critical role in nurses’ mental health. This study aimed to explore the prevalence of mood disorders and the impact of social factors, lifestyle on mood disorders among neonatal nurses. Methods: A total of 260 participants comprising neonatal nurses and nurses who work in neonatal intensive care units (NICU) were recruited. Data were collected using a validated generalized anxiety disorder questionnaire, patient health questionnaire-9, Pittsburgh sleep quality index, and social factors and lifestyle assessments. Results: In total, 49.23% of neonatal nurses exhibited mood disorders, particularly a combination of depression and anxiety. Female, poor interpersonal relationships and unhappy marital status, preference for smoking, alcohol, irregular diet, and poor sleep were common in neonatology nurses who exhibited mood disorders; preference for coffee and tea were lower in neonatology nurses without mood disorders (all P<0.05). Interpersonal relationships, marital status, irregular diet, and poor sleep were independent factors associated with mood disorders among neonatal nurses (all P<0.05). Mood disorders presented as functional dyspepsia (FD) among 50.78% of the participants (P<0.05). Poor sleep and preference for smoking were common among neonatal nurses who had FD with mood disorders (all P<0.05). Furthermore, the preference for sugary beverages was lower in participants with FD and mood disorders (P<0.05). Poor sleep was independently associated with FD with mood disorders in neonatology nurses (P<0.05). Conclusion: Prevalence of anxiety and depression was higher among neonatal nurses. Furthermore, most cases of mood disorders presented as FD. Thus, social factors and lifestyle have an impact on mood disorders which can manifest through somatic symptoms.